2009
DOI: 10.1016/j.drugalcdep.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Factors mediating and moderating the relationship between gender and utilization of health care among Puerto Rican drug users in New York

Abstract: This study examined factors that mediate and moderate the relationship between gender and utilization of mental health and medical services in the past year among Puerto Rican drug users (308 females; 892 males) recruited in New York City. Experience of sexual or physical abuse, injection drug use, relationship variables (e.g., having a sexual partner who is an injection drug user), and serious or chronic mental/medical conditions were used as potential mediators and moderators. Both sexual and physical abuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…We observed a huge service gap as over 70% of the participants had at least one type of unmet service needs. Similarly, prevalent unmet service needs among PWID have been reported in Western countries (Kang and Deren, 2009;Stein and Friedmann, 2002). This is understandable as PWID are a highly marginalized group in China and probably belong to one of the lowest social strata.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We observed a huge service gap as over 70% of the participants had at least one type of unmet service needs. Similarly, prevalent unmet service needs among PWID have been reported in Western countries (Kang and Deren, 2009;Stein and Friedmann, 2002). This is understandable as PWID are a highly marginalized group in China and probably belong to one of the lowest social strata.…”
Section: Discussionmentioning
confidence: 88%
“…In the USA, only 19% of male and 27% of female depressed substance users had utilized mental health services in the past year (Kang and Deren, 2009); 69.9-84.0% of the PWID who required mental health treatment reported an unmet need (Stein and Friedmann, 2002). Unmet needs for mental health services was associated with psychological distress among patients attending health centers (Jones et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, health insurance status was found to be significantly associated with using mental health services. 14 Because depression remains stigmatized in our society, participants may have been less likely to disclose a mental illness. However, reports of depression were consistent with other studies that have reported depression among illicit drug users.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,710 Despite the high prevalence of depression among IDUs and NIDUs and effective treatments for depression, 11,12 the use of mental health services among drug users is low. 13 In a sample of drug users in New York City, only 19% of depressed men and 27% of depressed women reported using mental health services in the past year 14 compared with 29% of depressed, non-substance users. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Sexual atrocities were/are also widespread during many of these Asian armed conflicts, and violence taking the form of mass rape and systems of sexual exploitation were/are also historically and currently entrenched within Asian heteropatriarchal systems in which girls and women in poverty were/are the most vulnerable (Chang, 1998;Cho, 2008;D'Costa, 2010;Hicks, 1995). The 60-plus year Korean War has still not ended and increasing evidence, including female North Korean survivor testimonies, indicate the rampant sexual violence, exploitation, and abuse perpetrated against North Korean girls and women, especially those girls and women classified by the DPRK in the "hostile" and "wavering" sectors (Chung, 2009), 14 by both the North Korean and Chinese nation-states (in which the 13 For racial stratification distinctions among Latino groups in the U.S., see Bonilla-Silva & Glover, 2004; it is interesting to note that these racial stratifications are also reflected in health disparities, such as which Latino groups are more vulnerable to injection drug use and survival sex work (Deren et al, 1997;Diaz et al, 2001;Friedman et al, 1998;Kang & Deren, 2009;Tortu et al, 1998). and hostile.…”
Section: Asian American Traumamentioning
confidence: 99%